Trends of HIV/AIDS Phenomenon Dynamics in Romania from 2017-2027 - Andrioni FELICIA (Tehran University of Medical Sciences, 2019)
Background: HIV infection remains of major public health importance in all world and in Romania. In Romania there are a large number of long-term survivors coming from the 1987-1990 generation, the circumstances are due to the fact that an increased number of HIV-infected persons receive a specific therapy. Methods: The study was conducted using sociological analysis methods such as comparative analysis, statistical analysis, and with the help of the method of regression analysis, to capture the dynamics of the HIV / AIDS phenomenon in Romania, as well as forecasting the dynamics of the phenomenon over the next decade. Results: This longitudinal analysis of the statistical data provided by the Matei Bals Institute of Romania during the period 2004-2016, shows a progressive increase 1.4 times higher in 2016 compared to 2004, the prediction of the extension of the HIV / AIDS phenomenon for the period 2017-2027, in Romania being almost constant. Regarding the prognosis of the number of persons affected by HIV / AIDS in Romania, for the next 10 years an upward dynamic is predicted with an increasing annual rate of 506 new persons taken into evidence. As the prediction function shows, the trend the access to treatment is increasing for the next decade. After 2006 in Romania, the deaths dynamics is an exponential decreasing one, keeping the same rate of decrease, until 2015. Conclusion: The HIV/AIDS pandemic has changed considerably in the past 27 years. AIDS incidence and mortality in industrialised countries have fallen, and paediatric HIV disease has almost been eliminated as a public health issue, largely through antiretroviral drugs.